Adenoma canalicular de glándulas salivales labiales: hallazgos histopatológicos e inmunohistoquímicos - Samar, Maria Elena; Ávila, Rodolfo Esteban; Dionisio de Cabalier, Mería Elisa; Fonseca, Ismael; Juri, Gustavo; Funes, Marta Susana (Asociación Panamericana de Anatomía, 2022)
2 p.